Membincang Ulang Komentar Nabi Tentang Wilayat Al-Mar'ah - Abdul Wahab (An-Nida : Jurnal Komunikasi Islam, 2018)
The study of wilāyat al-mar'ah is interesting to be explored given the many rigid interpretations of the hadith of the Prophet so as to imply discredit the ability of women. Through the language and historical analysis of the hadith of the prophet concerning wilāyat al-mar'ah it is found that: a) in the language perspective, the hadith about wilāyāt al-mar'ah can be interpreted that until whenever a people (wherever) will not succeed or prosper when handed over their (power) affairs to women (anywhere) to play a central role; b) The Prophet's comment on "women" let alone his power, for the writer can not be separated also by the condition of society that is "patriarchal". So for the sake of prosperity and "comfort" together, the tradition of male leadership must be preserved for a society which, during its history, positioned men as "rulers"; and c) the contextualisation of this study that the Apostle's commentary was not in terms of discrediting women, but in the context of his "pique" of Kisra's humiliation. Thus, this hadith can not be understood rigidly, even though its editorial "insults" and "cursing".